Relationship Between Breast Milk Ghrelin and Infants' Serum Ghrelin and Growth in Breastfeeding Infants: A Systematic Review and Meta-Analysis - Maryam Soori; Younes Mohammadi; Mohammad Taghi Goodarzi; Minoo Mahmoodi (Mazandaran University of Medical Sciences, 2020)
Background: There is positive correlation between infant serum ghrelin and the growth of infants in breastfed infants. Objectives: The present study aimed to evaluate of the relationship between breast milk ghrelin and serum ghrelin and growth in breast-milk-fed infants by systematic review and meta-analysis approaches. Methods: Electronic resources used in the current search were Scopus, Cochrane Library, Science Direct, PubMed, and EMBASE. The English language full-text articles and abstracts published from 1999 to July 2019 were collected. Only the articles that explored infants under two years of age and receiving breast milk exclusively were reviewed. Papers related to healthy mothers and infants were entered in this study. The results of 6 papers regarding the effect of serum ghrelin on the growth of infants, i.e., evaluated by meta-analysis using Stata software. The data addressing the effect of breast milk ghrelin on growth were reported by a systematic review manner; three articles were found in this area. We used Preferred Reporting Items for systematic reviews and meta-analyses (prisma) checklist for performing this study. Results: In this study, the association of infants' serum ghrelin with infants' growth was evaluated by meta-analysis. Newcastle-Ottawa Scale (NOS) value was ≥7scores for the 6 explored meta-analysis articles. The present meta-analysis research suggested a positive and significant correlation between infant serum ghrelin and the growth of infants (r=0.163).  Conclusions: The random-effect model data demonstrated a positive and significant correlation between infant serum ghrelin and the growth of infants. However, in the study of the effect of breast milk ghrelin on infants' growth, the number of articles was limited and contradictory results were reported. Accordingly, no general conclusion was reached.